THE IMPACT OF COFFEE CONSUMPTION ON HUMAN HEALTH: A REVIEW OF SCIENTIFIC EVIDENCE - Magdalena Adamik; Joanna Barwacz; Dagmara Gładysz; Layla Settaf-Cherif; Katarzyna Malinowska; Elhatra Settaf-Cherif (International Journal of Innovative Technologies in Social Science, 2025)
The purpose of this review is to present the current state of knowledge on the impact of coffee consumption on human health, with particular emphasis on its bioactive components and physiological effects. The method for the scientific literature review involved were the various systematic analyses, meta-analyses, and also the reports of global public health institutions like the European Food Safety Authority (EFSA) [7], the World Health Organization (WHO) [19], and the American College of Obstetricians and Gynecologists (ACOG) [1]. The theoretical section discusses the chemical composition of coffee, including caffeine, polyphenols, chlorogenic acids, and diterpenes, as well as their mechanisms of action on the nervous, metabolic, and cardiovascular systems. The review indicates that moderate coffee consumption (approximately two to four cups per day) is associated with a lower risk of type 2 diabetes, Parkinson’s disease, certain cancers, and reduced all-cause mortality [15][5]. Yet, overconsumption can cause sleep disorders, anxiety, acid reflux, and high blood pressure in people who are easily affected. Besides that, the review also points to factors that influence the impact of coffee on the body, such as the genetics of caffeine metabolism and the ways of preparation. Finally, it is stated that moderate consumption of coffee, particularly filtered, can be a safe practice and even have a positive effect on health. The main factors deciding this are the amount of coffee, the individual’s tolerance, and the general dietary and lifestyle context.